Fetal Zone Steroids Show Discrete Effects on Hyperoxia-Induced Attenuation of Migration in Cultured Oligodendrocyte Progenitor Cells. (9th May 2022) - Sunny, Donna E.; Krüger, Elisabeth L.; Hammer, Elke; Völker, Uwe; Heckmann, Matthias
Abstract : Cerebral oxygenation disturbances contribute to the pathogenesis of brain lesions in preterm infants with white matter damage. These children are at risk of developing long-term neurodevelopmental disabilities. Preterm birth is associated with sudden hormonal changes along with an untimely increase in oxygen tissue tension. There is a persistent high postnatal production of fetal zone steroids (FZS), which serve in the fetoplacental unit as precursors for placental estrogen synthesis during pregnancy. The role of FZS in events associated with oxygenation differences and their impact on the developing white matter is not well understood. Therefore, we investigated the effect of hyperoxia (80% O2 ) and subsequent administration of FZS on the protein composition and migration capabilities of immature oligodendrocytes using the OLN93 (rat-derived OPC) cell line as an experimental model. We tested the effect of the FZS, dehydroepiandrosterone (DHEA), 16 α -OH-DHEA, and adiol (5-androstene-3 β, 17 β -diol). After 24-hour exposure to hyperoxia, we monitored the changes in the proteome profile following treatment and observed significant alterations in pathways regulating cytoskeletal remodelling, cell migration, and cell survival. Additionally, hyperoxia leads to impaired migration of the OLN93 cells in culture. Administration of the FZS showed positive effects on the migration process under normoxic conditions in general. However, under hyperoxic conditions, the trend was less prominent. The observed effects could be related to changes in levels of cofilin/LIMK pathway-associated proteins. Adiol had a negative effect when administered together with estradiol, and the proteomic data reveal the activation of ephrin receptor signalling that might be responsible for the attenuation of migration. The results suggest that FZS can differentially regulate pathways involved in the migration of OLN93 cells. A deeper insight into the precise role of endogenous FZS would be an essential prerequisite for developing new treatment strategies including supplementation of estradiol and other steroids in preterm infants.